Survei Sarana Prasarana Pembelajaran Pendidikan Jasmani, Olahraga dan Kesehatan pada Sekolah Dasar Negeri Se-Kecamatan Balocci Kabupaten Pangkep - Tajuddin, Al Ihzan; Fufu, Ronald Dwi Adrian (Nusa Cendana University, 2021)
The need for physical education facilities and infrastructure in physical education learning is very vital, meaning that physical education learning must use facilities and infrastructure that suits the needs. This study aims to find out the number, condition and status of ownership of physical education, sports and health facilities and infrastructure in public elementary schools in Balocci Subdistrict, Pangkep Regency, South Sulawesi. This research is descriptive research with survey methods using observation sheet instruments. The population of this study used the subjects of all public elementary schools in Balocci Subdistrict Pangkep as many as 12 schools with the object of physical education, sports and health facilities. Data analysis techniques using quantitative descriptive analysis techniques are presented in the form of classifying the type of percentage data. Based on the analysis of data that has been done by data from the study, it can be concluded that in the category of 3 elementary schools with a percentage of 25%. Into a good category, there are 4 elementary schools with a percentage gain of 33.3%. And 2 elementary schools fall into the very good category with a percentage gain of 16.6%. So it can be concluded that physical education facilities and infrastructure are into a good category of 33.3%.